Deterministic and Stochastic Study of the X-Ray Emission from the TeV Blazar Mrk 421 - Radim Pánis; Gopal Bhatta; Tek P. Adhikari; Maksym Mohorian; Suvas Chandra Chaudhary; Adithiya Dinesh; Rajesh K. Bachchan; Niraj Dhital; Zdeněk Stuchlík (The Astrophysical Journal)
We present a comprehensive timing analysis of X-ray data from the XMM-Newton satellite, examining 50 light curves covering 17 yr of observations of the blazar Mrk 421. This work uses classical deterministic and stochastic methods in a novel way, enabling the distinction of temporal scales and offering essential insights through correlations among parameters. Deterministic behaviors are primarily explored through recurrence quantification analysis, used innovatively by varying the threshold input parameter to examine variability at multiple temporal scales. To investigate the behavior across various scales from a stochastic perspective, we apply both autoregressive moving average and autoregressive integrated moving average (ARIMA) models, with the results from ARIMA being more tightly related to short scales. Our findings reveal that Mrk 421’s X-ray emission is a multifaceted process, driven by both deterministic and stochastic patterns, indicating a complex interplay of physical phenomena. Our study demonstrates that deterministic patterns are more pronounced at small temporal scales, which are disconnected from large scales. On the other hand, stochastic processes with memory propagate from large to small timescales, while noise affects both scales, as indicated by the correlation analysis. These results underscore the importance of using advanced methodologies for interpreting astrophysical data, contributing to ongoing discussions in blazar physics by exploring connections between our calculated parameters and established models. The same approach can potentially be applied to other sources, enhancing our general understanding of the variability and emission mechanisms in blazars.